2015
DOI: 10.1103/physrevx.5.011021
|View full text |Cite
|
Sign up to set email alerts
|

Weak Ergodicity Breaking of Receptor Motion in Living Cells Stemming from Random Diffusivity

Abstract: Molecular transport in living systems regulates numerous processes underlying biological function.\ud Although many cellular components exhibit anomalous diffusion, only recently has the subdiffusive\ud motion been associated with nonergodic behavior. These findings have stimulated new questions for their\ud implications in statistical mechanics and cell biology. Is nonergodicity a common strategy shared by living\ud systems? Which physical mechanisms generate it? What are its implications for biological funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
273
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(313 citation statements)
references
References 56 publications
21
273
0
Order By: Relevance
“…50 and 51, where it was argued that the anomalous diffusion detected in dextran solutions was arising from the presence of different micro-environments. Similar interpretations have also been invoked in the case of intracellular diffusion: Recently, a spatially varying, random diffusivity 101 has been shown to be consistent with receptor motion in dendritic cells 102 .…”
Section: The Anomalous Yet Brownian Motion Of Proteins In Crowded Dementioning
confidence: 83%
“…50 and 51, where it was argued that the anomalous diffusion detected in dextran solutions was arising from the presence of different micro-environments. Similar interpretations have also been invoked in the case of intracellular diffusion: Recently, a spatially varying, random diffusivity 101 has been shown to be consistent with receptor motion in dendritic cells 102 .…”
Section: The Anomalous Yet Brownian Motion Of Proteins In Crowded Dementioning
confidence: 83%
“…The model discussed in this paper proposes a mechanistic explanation for the nonergodic subdiffusion observed in several biological systems [3][4][5][6][7], based on the occurrence of specific, transient interactions with a heterogeneous population of interacting partners. The model displays many similarities with the long-time behavior of the heavy-tail CTRW [9] and the patch model [19].…”
Section: Discussionmentioning
confidence: 99%
“…Such anomalous diffusion can have different physical origins and a large amount of models have been proposed for its interpretation, some of the most relevant ones being recently discussed by Metzler and co-workers [2]. The detailed analysis of the particle trajectories has shown that some processes characterized by anomalous diffusion also exhibit differences between ensemble and time averaged observables, such as the mean squared displacement itself [3][4][5][6][7]. This feature, known as weakergodicity breaking [8], reflects the physical nature of specific stochastic mechanisms, for which time averages are random and thus irreproducible in spite of the large statistics.…”
Section: Introductionmentioning
confidence: 99%
“…Other distributional behaviors have been found in other diffusion processes such as a quenched trap model [15,16] and stored-energy-driven Levy flight (SEDLF) [14,17], where the PDF of the normalized TMSDs (timeaveraged diffusion coefficients) follows other distributions depending on the power-law exponent in the waiting time distribution, the spatial dimension as well as parameters controlling jumps of a random walker. It is important to clarify whether fluctuations of time-averaged observables are intrinsic or not, because diffusion coefficients obtained by single-particle-tracking experiments in living cells exhibit large fluctuations [10,[18][19][20][21]. Such large fluctuations will have relevance to distributional behaviors in stochastic models of anomalous diffusion.…”
Section: Introductionmentioning
confidence: 99%